Studies of the Parasite-Midgut Interaction Reveal Plasmodium Proteins Important for Malaria Transmission to Mosquitoes - Niu, Guodong; Cui, Yingjun; Wang, Xiaohong; Keleta, Yacob; Li, Jun (Frontiers in Cellular and Infection Microbiology, 2021)
Malaria transmission relies on parasite-mosquito midgut interaction. The interactive proteins are hypothesized to be ideal targets to block malaria transmission to mosquitoes. We chose 76 genes that contain signal peptide-coding regions and are upregulated and highly abundant at sexual stages. Forty-six of these candidate genes (60%) were cloned and expressed using the baculovirus expression system in insect cells. Six of them, e.g., PF3D7_0303900, PF3D7_0406200 (Pfs16), PF3D7_1204400 (Pfs37), PF3D7_1214800, PF3D7_1239400, and PF3D7_1472800 were discovered to interact with blood-fed mosquito midgut lysate. Previous works showed that among these interactive proteins, knockout the orthologs of Pfs37 or Pfs16 in P. berghei reduced oocysts in mosquitoes. Here we further found that anti-Pfs16 polyclonal antibody significantly inhibited P. falciparum transmission to Anopheles gambiae. Investigating these candidate proteins will improve our understanding of malaria transmission and discover new targets to break malaria transmission.